Tua Pek Kong Procession And The Social Structure Of A Bazaar Community In Sarawak - Chai, Elena Gregoria Chin Fern (华社研究中心, 2012)
This paper examines the roles of religious beliefs in shaping the social structure of a bazaar community, hereafter named as Pekan. The community is made up of multi dialect Chinese setting predominated by Hakka. The Hakka are among the first of the Chinese dialect groups to have arrived at the bazaar. Despite their higher numbers in relation to population, the Hakka were sidelined in religious influences. On the other hand, the Teochew were the main force in religious activities. I study the social setting and religious exertions of this community to determine their influences on the social structure.